2018
DOI: 10.1007/s10055-018-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality crowd simulation: effects of agent density on user experience and behaviour

Abstract: Agent-based crowd simulations are used for modelling building and space usage, allowing designers to explore hypothetical real-world scenarios, including extraordinary events such as evacuations. Existing work which engages virtual reality (VR) as a platform for crowd simulations has been primarily focussed on the validation of simulation models through observation; the use of interactions such as gaze to enhance a sense of immersion; or studies of proxemics. In this work, we extend previous studies of proxemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 44 publications
2
28
0
Order By: Relevance
“…The theory of proxemics has been well studied in psychology and now being more and more used for VR experiments [151] [56] and computer scientists are just beginning to apply it to make more detailed models of the utility of pedestrian's personal space than simply collisions and non-collisions. In general, microscopic models are preferred to macroscopic models, in particular the social force model is very popular for pedestrian interaction modelling, while macroscopic models are more suited for crowd behaviour modeling, especially in the specialised domain of emergency evacuation modeling.…”
Section: Discussionmentioning
confidence: 99%
“…The theory of proxemics has been well studied in psychology and now being more and more used for VR experiments [151] [56] and computer scientists are just beginning to apply it to make more detailed models of the utility of pedestrian's personal space than simply collisions and non-collisions. In general, microscopic models are preferred to macroscopic models, in particular the social force model is very popular for pedestrian interaction modelling, while macroscopic models are more suited for crowd behaviour modeling, especially in the specialised domain of emergency evacuation modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Using a critical threshold of density to guide the decision to avoid a group of walkers, they proposed an adaptation of RVO model [62] to take into account the presence of groups in a crowd simulation. Finally, in a VR experiment, Dickinson et al recently reported that high crowd density has a negative influence on the affective state of participants, where the task was perceived as uncomfortable [16]. Authors also reported more direction changes and stops in the case of high density levels.…”
Section: Multiple Interactionsmentioning
confidence: 97%
“…The current study is an extension of previous studies that have examined human movement coordination in virtual environments [2,[18][19][20]62,63] and human-virtual-crowd interactions [59,61,[64][65][66]. However, less attention has been paid to understanding how humans coordinate their movement when surrounded by a crowd.…”
Section: Related Workmentioning
confidence: 99%
“…Among other human-crowd interaction studies, a virtual reality framework examining the human-virtual-crowd interaction and ways to improve the level of realism of simulation algorithms was developed by Olivier et al [58]. Dickinson et al [59] studied the effects of crowd density across three experimental conditions on the affective states and behaviors of participants. The results showed a significant increase in negative effects when interacting with a high-density crowd, measured using self-reported ratings.…”
Section: Related Workmentioning
confidence: 99%